2018
DOI: 10.21608/edj.2018.78446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Finishing and Polishing on Surface Roughness of Cubic Zirconia

Abstract: Aim:The purpose of this invitro study was to evaluate the effect of finishing and polishing on surface roughness of BruxZir Anterior Cubic zirconia before and after hydrothermal aging. Materials and methods:Twenty samples of BruxZir Anterior Cubic zirconia were divided into two groups, group (1): Polished BruxZir Anterior Cubic zirconia (n=10), group (2): Unpolished BruxZir Anterior Cubic zirconia (n=10). All samples were fabricated out of CAD CAM blocks and evaluated for surface roughness before and after hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…56 Standardization of aging procedure was done according to standard aging protocol of ISO13356 by autoclaving zirconia samples of both groups at temperature of 134 o C and 2 bar pressure for 5 hours simulating 15 years serviceability. 57 This strategy was in accordance with another studies that mentioned the reliability of using autoclave to simulate oral conditions. 15,38,58 The present study revealed that IPS e.max ZirCAD Prime showed significantly lower mean Ra before accelerated hydrothermal aging than BruxZir.…”
supporting
confidence: 83%
“…56 Standardization of aging procedure was done according to standard aging protocol of ISO13356 by autoclaving zirconia samples of both groups at temperature of 134 o C and 2 bar pressure for 5 hours simulating 15 years serviceability. 57 This strategy was in accordance with another studies that mentioned the reliability of using autoclave to simulate oral conditions. 15,38,58 The present study revealed that IPS e.max ZirCAD Prime showed significantly lower mean Ra before accelerated hydrothermal aging than BruxZir.…”
supporting
confidence: 83%